Dinamika pemikiran intelektual muslim dalam penafsiran Al-qur’an - Ahmad Zaini Dahlan; Fawaz Fawaz (Al Irfani: Journal of Al Qur'anic and Tafsir, 2022)
Allah SWT has created humans to be the best of creation (ahsan at-taqwim), namely beings who are given reason and lust. Humans as intelligent creatures are ordered by Allah to use their intellect. Regarding the command to use human reason in the Al-Qur'an, there is much mention of the words afala tatadzabbarun, afala taqqilu, afal tatafakkarun, ya ulil albab and so on. The end of these verses relates to the command to think about Allah's creation. Neither man himself nor the universe. However, awareness of history and the contextuality of human understanding in using their minds intersect with the texts of the al-Qur'an and their meanings. In fact, it is generally agreed that the Muslim intellectual believes that the Koran is sacred because the Qur'an is one of the words of Allah that was revealed to the last prophet, Muhammad SAW. After seeing the historical facts that the Qur'an uses Arabic and the Prophet Muhammad SAW himself was an Arab. So that the various information presented in the Koran itself uses a lot of Arabic cultural logic, then the various terms used in it also use terminology that is familiar to Arabic at that time, so various studies and discussions about the original status of the Qur'an have emerged. 'an. Here the question arises as put forward by Fahrudi Faiz "to what extent the Qur'an is divine and to what extent it has a human dimension